Dinamika Dakwah dalam Membangun Karakter Anak di LPKA Kelas I Medan - Ainul Mardiyah; Ananda Maulidza; Ihdina Syafa Muhayya; Muhammad Fadillah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Children's da'wah at LPKA Class I Medan has an important role in building children's character with noble morals. Through creative and innovative preaching dynamics, children are taught religious values ​​that can be applied in everyday life. This research aims to analyze the dynamics of da'wah in building children's character in LPKA Class I Medan. This research uses a qualitative method with a descriptive approach. Data was collected through observation and interviews. The research results show that the dynamics of da'wah in LPKA Class I Medan is carried out using various methods, such as lectures, group discussions, educational games, and simulations. The preaching material taught includes the definition and types of uncleanliness, sources and examples of uncleanness, laws and procedures for purification, the role of cleanliness in faith, and application in daily life. Da'wah at LPKA Class I Medan has a significant influence on the formation of children's character. Religious values ​​conveyed through da'wah help children develop good personalities and noble morals. By implementing appropriate and consistent strategies, it is hoped that LPKA Class I Medan can become an effective educational institution in building the character of children who have noble character and faith in Allah SWT.